Dynamic Effect of Moving Vehicles on the Road Concrete Slabs - Lajcakova, Gabriela; Melcer, Jozef (Communications - Scientific letters of the University of Zilina, 2011)
The road concrete slabs represent the typical transport structure exposed to dynamic effects of moving vehicles. Numerical simulation methods demand to pay attention to the proposal of the computing model of the vehicle and the computing model of the road concrete slab. The models must be mathematically described and the equations of motion must be solved in a numerical way. For the solution of such a problem the specialized computer program must be created. It is suitable to use the possibilities of the higher level programming languages as MATLAB. The influence of some important factors on dynamic response of the structure is numerically tested.